Effect of alkaloid extract from Andrographis paniculata (Burm. f.) Nees and Phyllanthus amarus Schumach. & Thonn. on cognitive related biochemicals in the brain of streptozotocin-induced diabetic rats - Bukola C. Adedayo; Oluwapelumi M. Ajiboye; Idowu S. Oyeleye; Raymond O. Ojo; Ganiyu Oboh (Elsevier, 2023)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disorder linked to cognitive impairment and memory deficit, known as diabetes encephalopathy. This study examined the anti-diabetic and neuroprotective effects of alkaloid extracts from Andrographis paniculata (A. paniculata) and Phyllanthus amarus (P. amarus) leaves, a Traditional Chinese Medicine, on carbohydrate-metabolizing (α-amylase and α-glucosidase) enzyme, cholinesterase and purinergic enzyme activities, and antioxidants in the brains of streptozotocin (STZ)-induced diabetic rats. Methods: The alkaloid extraction of A. paniculata and P. amarus was done. Male Wistar rats were divided into seven groups (n = 5) and were made diabetic by intraperitoneal injection of 50 mg/kg of STZ except Group I, which received saline (normal control). Group II-untreated diabetic rats (diabetic control), Group III-diabetic rats received 5 mg/kg Glibenclamide (standard drug); Group IV and V received 5 and 50 mg/kg P. amarus respectively; and Group VI and VII received 5 and 50 mg/kg A. paniculata, respectively. Results: The results showed that the elevated blood glucose and redox makers levels and enzyme activities were significantly increased in the untreated diabetic rats. Reduced antioxidant biomolecules (enzymatic and non-enzymatic antioxidant) levels were also observed. However, these were considerably ameliorated upon treatment with the alkaloid extracts in a dose-dependent manner. Conclusion: The study found that the alkaloid extract of P. amarus and A. paniculata leaves can modulate cognitive functioning and antioxidant profile in STZ-induced diabetic rats, suggesting it could be a promising alternative for managing diabetes and its complications, including cognitive impairment, in the treatment of diabetes and diabetes encephalopathy.